Can occupational safety and health problems be prevented or not? Exploring the perception of informal automobile artisans in Nigeria. (March 2021) - Afolabi, Funmilayo Juliana; de Beer, Paul; Haafkens, Joke A.
Highlights: The perception of preventability of OSH problems is related to perceived causes. OSH problems caused by work-worker-related factors are often considered preventable. OSH problems attributed to religious/cultural beliefs were seen as unpreventable. Economic insecurity is the major perceived barrier to OSH problems prevention. Abstract: It is well-known that informal workers in developing countries run a high risk of Occupational Safety and Health Problems (OSH problems). However, little is known about their perception of the preventability of these problems. This study explores how informal automobile artisans in Nigeria perceive the preventability of OSH problems and possible barriers to prevention. 43 artisans were purposively interviewed. Only one third of the participants perceived OSH problems as preventable while a majority perceived OSH problems as not preventable. Their perception of the causes of OSH problems and cost considerations strongly influenced their perceptions of the preventability of OSH problems. The major perceived barrier to prevention is economic insecurity and, as a consequence, non-availability of modern equipment. The study concluded that availability of accessible loans and regular training of the artisans may be helpful in preventing and reducing OSH problems in the informal sector.